What can be done to reduce the prevalence of teen pregnancy in rural Eastern Uganda?: multi-stakeholder perceptions - Josephine Nabugoomu; Gloria K. Seruwagi; Rhona Hanning (BMC, 2020)
Abstract Introduction The teenage pregnancy rate of 25% in Uganda is worrying though it may seem low compared to 28% in Sub-Saharan countries and West and Central Africa. Young mothers in Uganda risk poor maternal and child health, being isolated, attempting unsafe abortions, failure to continue with school, and poverty. This paper describes perceptions and recommendations of young mothers, family and community members on why the high rate of teenage pregnancies in Uganda and how these can be reduced. Methods This qualitative research was conducted from March to May 2016 in six communities within Budondo sub-county (Jinja district), Eastern Uganda. In-depth oral interviews were conducted with 101 purposively sampled adolescent mothers, family members, and workers of government and non-government organizations. Thematic analysis framed around levels of influence within a social cognitive framework was conducted using Atlas-ti (version 7.5.4). Results Perceived determinants of teenage pregnancies include: lack of life and social survival skills, lack of knowledge on how to avoid pregnancy, low acceptance/use of contraceptives, neglect by parents, sexual abuse, pressure to contribute to family welfare through early marriage or sexual transactions, lack of community responsibility, media influence, peer pressure, cultural beliefs that promote early marriage/childbearing and lack of role models. Other contributing factors include drug use among boys, poverty, late work hours, long travel distances, e.g., to school, and unsupervised locations like sugarcane plantation thickets. Recommendations participants offered include: sensitization seminars and counselling for parents and girls, closing pornography outlets that accept entrance of minors, using the law to punish rapists, involvement of the President to campaign against early pregnancies, school dismissal before dark, locally accessible schools and job creation for parents to earn money to support the girls financially. Areas for capacity building are: training teachers and community members in transferring empowerment and vocational skills to girls, and construction of homes with separate rooms to support parents' privacy. Conclusion The factors associated with adolescent pregnancy in Uganda fall under individual, economic, social and physical environmental determinants. Recommendations spanning family, community and government involvement can ultimately empower girls, their families and community members, and support collective action to reduce teenage pregnancies.